Antioxidant properties of wood extracts and colour stability of woods - Diouf, Papa-Niokhor; Merlin, André; Perrin, Dominique (Ann. For. Sci., 2006)
Industrial wood extracts were selected and other extracts were prepared in the laboratory from some chosen wood species. Antioxidant capacities of extracts were measured by three methods: the oxygen uptake method, the kinetic DPPH method, and the equilibrium DPPH method. There is a fair correlation between the three methods. Total phenol contents of the extracts and colour stability of woods were measured. For the same phenol content, extracts containing condensed tannins are more antioxidant than those containing hydrolysable tannins. Colour stability is clearly correlated neither with phenol content nor with antioxidant capacity of the extracts, but it is conferred to non durable woods if impregnated with extracts of durable species. Light aging is accompanied by consumption of the most antioxidant compounds of the extracts first.
Keywords: antioxidant; colour; extract; polyphenol; tannin; Wood

Antioxidant properties of wood extracts and colour stability of woods - Diouf, Papa-Niokhor; Merlin, André; Perrin, Dominique (Ann. For. Sci., 2006)
Industrial wood extracts were selected and other extracts were prepared in the laboratory from some chosen wood species. Antioxidant capacities of extracts were measured by three methods: the oxygen uptake method, the kinetic DPPH method, and the equilibrium DPPH method. There is a fair correlation between the three methods. Total phenol contents of the extracts and colour stability of woods were measured. For the same phenol content, extracts containing condensed tannins are more antioxidant than those containing hydrolysable tannins. Colour stability is clearly correlated neither with phenol content nor with antioxidant capacity of the extracts, but it is conferred to non durable woods if impregnated with extracts of durable species. Light aging is accompanied by consumption of the most antioxidant compounds of the extracts first.
Keywords: antioxidant; colour; extract; polyphenol; tannin; Wood